Tribological Behavior of Ni-P Electroless Coating of Inconel 625 with Multiwall Nano Carbon Tubes - D. Jayabalakrishnan; S. Senthil Kumar; R. Suthan; P. Babu Aurtherson; J. Elanchezhian; V. Ramanareddy; S. Louies Praveen; null Umamahesawari Kandasamy (Advances in Materials Science and Engineering)
An attempt was taken to study the wear rate of coated Inconel 625 using 0.3 gm of multiwall carbon tubes (MWCNT).The coating was carried out by the Ni-P electroless coating method. The Ni-P-MWCNT coating was prepared by using nickel phosphorous solution. The sliding wear test was conducted using pin on discs tribometer. The wear rate behavior was investigated at various levels of pin on discs tribometer factors, and a predictive model was developed using regression equations. The wear test experiment was carried out based on the L27 orthogonal array. The wear process parameters load, sliding velocity, and sliding distance were chosen. It was observed that the rate of wear increased as the load increases, whereas increase in sliding velocity and sliding distance reduces the rate of wear. The developed regression model was validated with the measured wear rate. The percentage error was observed within 0.99%.